Malignant Melanoma of Anal Canal - Dhungana, Ishan; Bhatta, Ranjan Raj; Pandey, Greta; Upreti, Suraj; Shah, Nadita; Bastakoti, Shankar (Nepalese Journal of Cancer, 2021)
Anal melanoma (AM) is a rare and highly aggressive mucosal melanocytic malignancy. We report a case of 70 year old male presented with chief complaints of anal pain and intermittent rectal bleeding with clinical diagnosis of Polyp or Carcinoma. On histopathology examination malignant melanoma was suggested which was further confirmed by immunohistochemistry (S100 and HMB 45 strongly positive). Anal melanoma is rare neoplastic condition with catastrophic outcome.